2014
DOI: 10.1155/2014/202876
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gynostemma pentaphyllum Extract on Mouse Dermal Fibroblasts

Abstract: Background. The objective of this paper is to demonstrate the effect of Gynostemma pentaphyllum extract on mouse dermal fibroblasts. Recent studies have shown that this plant may possess great antioxidant properties, which can be very beneficial in combating oxidative stress. Methods. Gynostemma pentaphyllum extract was prepared and mouse dermal fibroblasts were obtained and cultured as per our laboratory protocols. Twelve samples of cells were cultured under the same conditions and both negative and positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…According to Figure 2A, we first applied gradient condition I below 0-20 min, 10% A; 50 min, 20% A; 70 min, 22% A; 110 min, 24% A; 140 min, 30%A; 180 min, 36%A; 190-240 min, 60%A, with the 5.0 mL/min flow rate and 70 mg sample loading. The results showed that it was first separated into two fractions and a pure compound (5), indicating a bit strong elution capacity. Then, the gradient condition II was used to increase the peak separation efficiency, as shown below, 0-20 min, 10% A; 50-100 min, 20% A; 110-140 min, 30% A; 160-240 min, 60%A.…”
Section: Results Of Parameter Selection and Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Figure 2A, we first applied gradient condition I below 0-20 min, 10% A; 50 min, 20% A; 70 min, 22% A; 110 min, 24% A; 140 min, 30%A; 180 min, 36%A; 190-240 min, 60%A, with the 5.0 mL/min flow rate and 70 mg sample loading. The results showed that it was first separated into two fractions and a pure compound (5), indicating a bit strong elution capacity. Then, the gradient condition II was used to increase the peak separation efficiency, as shown below, 0-20 min, 10% A; 50-100 min, 20% A; 110-140 min, 30% A; 160-240 min, 60%A.…”
Section: Results Of Parameter Selection and Separationmentioning
confidence: 99%
“…Makino, which belongs to the Cucurbitaceae family, has long been used in supplemental products and foods in Asian countries [1]. Gynostemma pentaphyllum is recently reported to possess various biological functions such as anticancer [2], neuroprotection [3], antidiabetes [4], antioxidation [5], immune stimulation [6], and anti‐inflammation [7]. Phytochemical investigations indicate that highly polar glycosides, including flavonoids and saponins, are the major effective ingredients related to the diversified pharmacological activities of G. pentaphyllum [8].…”
Section: Introductionmentioning
confidence: 99%
“…After 8 weeks of intraperitoneal injection of 100 mg/kg/d d-galactose to establish a rat model of aging with different doses of Ganoderma lucidum extract, it was found that Ganoderma lucidum could delay the progression of AD by regulating DNA methylation [207]. Lobo et al [208] gave different concentrations (0.5-5.0 mg/mL) of the Gynostemma pentaphyllum extract to mouse dermal fibroblasts, which were placed under 8-watt ultraviolet C (UVC) light at a distance of 50 cm to induce oxidative stress. The results showed that Gynostemma pentaphyllum extract prolongs viability of mouse dermal fibroblasts damaged by UVC light-induced oxidative stress, especially at 4.5 mg/mL, and it suggested that Gynostemma pentaphyllum extract had potential therapeutic effect on dermal cell aging.…”
Section: Angelica Sinensis (Danggui) the Active Components Ofmentioning
confidence: 99%
“…GP extract has been reported to affect cell and animal models of several diseases such as chronic liver disease 8 , dermal cell aging 9 , obesity 10 , and cancer 11 . GP has been proposed to correlate with multiple signaling pathways, including apoptosis, cell cycle arrest, inhibition of glycolysis, immunomodulatory activity, and antioxidant activity by upregulating SIRT1 and regulating the EGFR/PI3K/Akt signaling pathway 10 , 12 .…”
Section: Introductionmentioning
confidence: 99%